2014
DOI: 10.3732/apps.1400017
|View full text |Cite
|
Sign up to set email alerts
|

Sequence‐related amplified polymorphism (SRAP) markers: A potential resource for studies in plant molecular biology1

Abstract: In the past few decades, many investigations in the field of plant biology have employed selectively neutral, multilocus, dominant markers such as inter-simple sequence repeat (ISSR), random-amplified polymorphic DNA (RAPD), and amplified fragment length polymorphism (AFLP) to address hypotheses at lower taxonomic levels. More recently, sequence-related amplified polymorphism (SRAP) markers have been developed, which are used to amplify coding regions of DNA with primers targeting open reading frames. These ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
89
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(98 citation statements)
references
References 195 publications
(258 reference statements)
7
89
0
2
Order By: Relevance
“…These results make SRAP markers choice markers for the study of functional polymorphism that is directly related to transcriptomic data. Furthermore, the results support information from Robarts and Wolfe (2014), which proposed "that use of SRAP markers should be viewed analogous to morphological character states".…”
Section: Discussionsupporting
confidence: 68%
“…These results make SRAP markers choice markers for the study of functional polymorphism that is directly related to transcriptomic data. Furthermore, the results support information from Robarts and Wolfe (2014), which proposed "that use of SRAP markers should be viewed analogous to morphological character states".…”
Section: Discussionsupporting
confidence: 68%
“…Recently, Li et al, (2013) recommended that SRAP has advantages with a wide range of applications in plant breeding over other molecular detection techniques in gene tagging and cloning and allows screening thousands of loci shortly to pinpoint the genetic position underlying the trait of interest. Our results approved with several research article confirmed that an SRAP marker had the greatest discrimination capacity of polymorphism, and results in a moderate number of co-dominant markers with efficient in marker assisted selection in plant breeding and genetic diversity of many plant species (Agarwal et al, 2008;Dong et al, 2010;Li et al, 2010;Aneja et al, 2012;Robarts and Wolfe 2014).…”
Section: Discussionsupporting
confidence: 67%
“…Other studies in several plants have also confirmed that SRAP is superior information than other methods, for example, RAPD (Liu et al, 2007), ISSR (LiWang et al, 2008) and SSR . Recently, Robarts and Wolfe (2014) propose that SRAP markers should be employed for research addressing hypotheses in plant systematics and these markers have verified to be robust and highly variable, on par with AFLP. On behalf of the behavior of ISSR profile, the level of polymorphism is relatively high; this is probably due to the value of the effective number of patterns per assay units.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the opposite, SRAP results seam more trustworthy, as they have the highest average discriminating power among the four systems AFLP, SSR, ISSR, and RAPD (Budak, Shearman, Parmaksiz, Gaussoin, & Riosdan, 2004). Furthermore, SRAP markers have the asset to amplify coding regions of the genome with primers targeting ORFs, elucidating therefore regions with inherent biological significance (Robarts, & Wolfe, 2014).…”
Section: Discussmentioning
confidence: 99%